Leading Change while Managing Conflict in Departmental Transitions - Michelle M Proctor; Karent Ross (Academic Chairpersons Conference Proceedings, 2015)
This session will explore conflict management strategies utilized while redefining a department during reaccreditation. Case examples of approaches used and results achieved will be presented in relation to existing literature. Through group activities, participants will be invited to explore and discuss the effectiveness of strategies used in each example presented.
Keywords: Administrative Leadership; Conflict Management; Departmental Transition; Community